Investigation of CYP3A induction by PF‐05251749 in early clinical development: comparison of linear slope physiologically based pharmacokinetic prediction and biomarker response. Issue 9 (2nd July 2022) - Lin, Jian; Gaudreault, Francois; Johnson, Nathaniel; Lin, Zhiwu; Nouri, Parya; Goosen, Theunis C.; Sawant‐Basak, Aarti
Abstract: PF‐05251749 is a dual inhibitor of casein kinase 1 δ/ε under clinical development to treat disruption of circadian rhythm in Alzheimer's and Parkinson's diseases. In vitro, PF‐05251749 (0.3–100 μM) induced CYP3A in cryopreserved human hepatocytes, demonstrating non‐saturable, dose–dependent CYP3A mRNA increases, with induction slopes in the range 0.036–0.39 μM −1 . In a multiple‐dose study (B8001002) in healthy participants, CYP3A activity was explored by measuring changes in 4β‐hydroxycholesterol/cholesterol ratio. Following repeated oral administration of PF‐05251749, up to 400 mg q.d., no significant changes were observed in 4β‐hydroxycholesterol/cholesterol ratio; this ratio increased significantly (~1.5‐fold) following administration of PF‐05251749 at 750 mg q.d., suggesting potential CYP3A induction at this dose. Physiologically based pharmacokinetic (PBPK) models were developed to characterize the observed clinical pharmacokinetics (PK) of PF‐05251749 at 400 and 750 mg q.d.; the PBPK induction model was calibrated using the in vitro linear fit induction slope, with rifampin as reference compound (Indmax  = 8, EC50  = 0.32 μM). Clinical trial simulation following co‐administration of PF‐05251749, 400 mg q.d. with oral midazolam 2 mg, predicted no significant drug interaction risk. PBPK model predicted weak drug interaction following co‐administration of PF‐05251749, 750 mg q.d. with midazolam 2 mg. In conclusion, good agreement was obtained between CYP3A drug interaction risk predicted using linear‐slope PBPK model and exploratory biomarker trends. This agreement between two orthogonal approaches enabled assessment of drug interaction risks of PF‐05251749 in early clinical development, in the absence of a clinical drug–drug interaction study.